Coexistence of urethritis with genital ulcer disease in South Africa: influence on provision of syndromic management. Issue 4 (1st August 2002) - Ballard, R C; Fehler, H G; Htun, Y; Radebe, F; Jensen, J S; Taylor-Robinson, D
Abstract : Objective: To assess whether syndromic management of genital ulcer disease was sound, if based on the premise that men with genital ulcers rarely have a concomitant urethral infection. Methods: Specimens were taken in 1998 from 186 mine workers in Carletonville, South Africa, who were seen consecutively with genital ulcers. The specimens comprised a swab from the ulcer, a urethral swab for a Gram stained smear, and 10–15 ml of a first catch urine sample. The latter was tested by ligase chain reaction assays for Neisseria gonorrhoeae and Chlamydia trachomatis specific DNA sequences and by a polymerase chain reaction (PCR) assay for Mycoplasma genitalium . Ulcer inducing micro-organisms were detected either by a multiplex PCR assay, or in the case of lymphogranuloma venereum (LGV) serologically, and human immunodeficiency virus (HIV) infection was detected by an enzyme linked immunosorbent assay (ELISA) test. Results: Most (54%) of the ulcers were chancroidal, 18% were herpetic (HSV type 2), 6.5% primary syphilitic, and 3.2% due to LGV. More than one micro-organism was detected in 9.1% of the ulcers and less than 10% were undiagnosed. Microscopic examination of the urethral smears showed that 99 (53%) of the men had urethritis, of whom 45 (45%) were infected with N gonorrhoeae . Of the 54 men (55%) who had non-gonococcal urethritis (NGU), 11 (19.6%) harboured C trachomatis or M genitalium. Almost two thirds (64.5%) of the men had HIV infection, but this did not seem to have influenced the aetiology of the ulcers. Nor was a particular ulcer associated with one type of urethritis more than the other. Neither C trachomatis nor M genitalium was associated significantly with non-gonococcal urethritis (NGU) in either HIV positive or HIV negative men. Conclusion: The combination of antibiotics used for the management of genital ulcer disease in men in this South African mining population needs to be widened to encompass frequently occurring concomitant gonococcal urethritis and NGU infections. This means treatment with long acting penicillin, combined with ciprofloxacin and azithromycin or erythromycin. A similar situation may exist in other geographical locations with a need to provide appropriate antimicrobial combinations depending on the patterns of infection detected.